The internal auditing the organizational culture and its specificity within the international standards for the professional practice: Analytical theory study - Mouna Kechat (Advanced Research in Economics and Business Strategy Journal)
The purpose of this study is to clarify how to audit organizational culture in accordance with the International Standards for Professional Practice issued by the Institute of Internal Auditors (IIA) in the United States.